Sovereign atonement citizenship, territory, and the state at the Bangladesh-India border - Ferdoush, Md. Azmeary (South Asia in the social sciences, 2024)
The former border enclaves of Bangladesh and India existed as extra-territorial spaces since 1947. They were finally exchanged and merged as host state territories in 2015. Sovereign Atonement focuses on the protracted territorial exchange and experiences of the newly accepted Bangladeshi citizens. It grapples with one broad question: why did the state assume an active role in smoothing the once excluded population's experiences into their inclusion within the sovereign project? The book dives deep into an ethnographic and historical reading of the everyday state, land and territory, informality, (non)state actors, and performance of sovereignty. Furthermore, it troubles the often taken-for-granted understanding of exception, governance, and citizenship. As such, Ferdoush offers a retake on the two seemingly contradictory concepts -'sovereign' and 'atonement'- to demonstrate that bridged together these concepts as sovereign atonement enables a novel way of appreciating geopolitical narratives, political geographies, and nationalistic discourse in South Asia and beyond